- Uji Efektivitas Formulasi Sabun Cuci Piring Berbahan Dasar Ekstraksi Kulit Buah Nangka (Artocarpus heterophyllus) Dengan Penambahan Gel Lidah Buaya dan Jeruk Kasturi: Uji Efektivitas Formulasi Sabun Cuci Piring Berbahan Dasar Ekstraksi Kulit Buah Nangka (Artocarpus heterophyllus) Dengan Penambahan Gel Lidah Buaya dan Jeruk Kasturi - Ariyani, Silla; Rambitan, Vandalita M.M.; Lumowa, Herliani, Sonja V.T. (UNIB Press, 2026)
This study aimed to formulate and evaluate an eco-friendly dishwashing liquid made from jackfruit peel (Artocarpus heterophyllus) extract with the addition of aloe vera gel and calamansi juice. The extract was obtained through ethanol maceration and formulated at different concentrations. Product evaluation included organoleptic properties, homogeneity, pH, viscosity, foam stability, and antibacterial activity against Staphylococcus aureus. The results showed that the formulation produced a dishwashing liquid with good physical characteristics, antibacterial effectiveness, and safety for use. In addition to its potential as an environmentally friendly cleaning agent, this product can be utilized as contextual biotechnology learning material for senior high school students.